2018
DOI: 10.1038/nature25475
|View full text |Cite|
|
Sign up to set email alerts
|

HER kinase inhibition in patients with HER2- and HER3-mutant cancers

Abstract: Summary Somatic mutations of ERBB2 (HER2) and ERBB3 (HER3) are found in a wide range of cancers. Preclinical modelling suggests that a subset lead to constitutive HER2 activation, but most remain biologically uncharacterized. We sought to prospectively define the biologic and therapeutic significance of known oncogenic HER2 and HER3 mutations and variants of unknown biological significance by conducting a multi-histology, genomically selected, ‘basket’ study utilizing the pan-HER kinase inhibitor neratinib (SU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
545
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 630 publications
(589 citation statements)
references
References 53 publications
14
545
0
3
Order By: Relevance
“…By contrast, other first-, second-, and third-generation TKIs had IC 50 values that were above the clinically achievable plasma concentrations previously observed in patients 31,41,42,43,44,45 . In concordance with this, clinical testing of afatinib, neratinib, and dacomitinib achieved overall response rates of 8.7%, 9.5%, and 12%, respectively, for patients harboring EGFR or HER2 exon 20 mutations 25,42,46,47 . Here, we report that in vitro, poziotinib is approximately 40 times more potent than afatinib and 65 times more potent than dacomitinib in cell lines bearing EGFR exon 20 mutants.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…By contrast, other first-, second-, and third-generation TKIs had IC 50 values that were above the clinically achievable plasma concentrations previously observed in patients 31,41,42,43,44,45 . In concordance with this, clinical testing of afatinib, neratinib, and dacomitinib achieved overall response rates of 8.7%, 9.5%, and 12%, respectively, for patients harboring EGFR or HER2 exon 20 mutations 25,42,46,47 . Here, we report that in vitro, poziotinib is approximately 40 times more potent than afatinib and 65 times more potent than dacomitinib in cell lines bearing EGFR exon 20 mutants.…”
Section: Discussionsupporting
confidence: 67%
“…Together, EGFR and HER2 exon 20 mutations are found in approximately 4% of all patients with NSCLC 19 . The data thus far suggest that TKIs targeting HER2 (afatinib, lapatinib, neratinib, dacomitinib) have limited activity in patients with HER2-mutant tumors, with objective response rates (ORRs) of below 40% reported by many studies 19,20,21,22,23,25 , although some preclinical activity was observed in mouse models bearing mutated HER2 that were treated with afatinib 26 .…”
mentioning
confidence: 99%
“…Many countries have a long history of subsidizing fossil fuels, and it seems logical that removing these subsidies -as the G20 group of nations has agreed to do -would help them to achieve their Paris climate commitments. However, on page 229, Jewell et al 1 report a comprehensive and convincing analysis suggesting that reforming these subsidies would cause only a modest reduction in global CO 2 emissions. Nevertheless, I think that there is an urgent need for broader reform of fossilfuel prices to fully reflect the costs associated with global warming and other environmental considerations.…”
mentioning
confidence: 99%
“…And could it treat a person with a mutation in the same gene, but in a tumour that has developed in a different tissue? On page 189, Hyman et al 1 report the outcome of a clinical trial testing the ability of the drug neratinib, which inhibits HER2 and HER3 tyrosine kinase enzymes, to reduce or eliminate tumours. The drug was tested on 21 types of cancer in 141 people who had a total of 42 different mutations affecting one of the enzymes.…”
mentioning
confidence: 99%
See 1 more Smart Citation